ADAPTABILITY OF EXTENDED REALITY (XR) FOR MARKETING - AUDIENCE’S PERSPECTIVE ON IMMERSIVE EXPERIENCE DELIVERED THROUGH EXTENDED REALITY (XR) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Since last few years technical advancements  have opened new doors for marketers. Extended  Reality(XR), a board term representing  Mixed Reality(MR), Virtual Reality(VR)  and Augmented Reality(AR) (Milgram &  Kishino, 1994); is an emerging integration of  IT and Marketing that delivers meaningful  results to marketing strategies by delivering  immersive product experience to audiences. In  continuation of past researches on Extended  Reality, this study is exclusively focused  on awareness, likability, acceptability and  feasibility of Extended Reality for marketing  communication tool, keeping audience’s  perspectives at center. Research findings are  primarily based on data collected through  structured questionnaire and supported  through literature review. 150 numbers of  respondents were asked with series of questions  strategically designed to achieve research  objectives. Research study is concluded with  further scope of study in subject discipline.
Keywords: Extended Reality(XR); Mixed Reality(MR); Virtual Reality(VR); Augmented; Reality(AR); Marketing Communication